Political entrepreneurs, clientelism, and civil society: supply-side politics in Turkey. Issue 4 (6th June 2016) - Ocakli, Feryaz
Abstract : How do citizens in developing democracies launch political careers? Despite the large literature on electoral politics in developing countries, we know surprisingly little about how individuals become political candidates. This article examines an important mechanism of political recruitment in developing democracies: party-civil society organization (CSO) linkages. Existing theories treat CSOs as arenas of civic participation rather than as political agents in their own right, which leads scholars to overlook their impact on electoral competition. This article argues that the distinct resource portfolios of CSOs influence their relative impact on candidate selection, and consequently, local politics. CSOs that represent the material interests of their constituents, such as resource-rich business groups and vote-rich identity groups, have significant influence over candidate selection. Issue-oriented CSOs tend to have less impact. Party-CSO relations often facilitate clientelist linkages between parties and voters, weakening democratic governance. Evidence is provided with an in-depth case study of CSO-political party relations in the industrial periphery of Istanbul, Turkey.